Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d0lc01006e
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging-based exosome microarray for rapid molecular profiling of extracellular vesicles

Abstract: One of the challenges for exploiting extracellular vesicle (EV) as a disease biomarker is to differentiate EVs released by similar cell types or phenotypes. The paper reports a high-throughput and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The PC biosensor measures the change of the refractive index induced by the adsorption of biomaterials onto its surface. [27][28][29] Here, the nanoreplica molding approach was used to replicate the 1D PC structure from a 555.5 nm-period silicon grating (LightSmyth Technologies) to an optical adhesive (NOA 86, Norland Products) on a 180 μm-thick plastic sheet. A 100 nm TiO 2 thin film was coated on the replicated grating using an electron beam evaporator.…”
Section: Preparation Of Pc Biosensorsmentioning
confidence: 99%
“…The PC biosensor measures the change of the refractive index induced by the adsorption of biomaterials onto its surface. [27][28][29] Here, the nanoreplica molding approach was used to replicate the 1D PC structure from a 555.5 nm-period silicon grating (LightSmyth Technologies) to an optical adhesive (NOA 86, Norland Products) on a 180 μm-thick plastic sheet. A 100 nm TiO 2 thin film was coated on the replicated grating using an electron beam evaporator.…”
Section: Preparation Of Pc Biosensorsmentioning
confidence: 99%
“…41 These membrane markers have been used to distinguish macrophage-derived EV subtypes. 42 Three different PC biosensors were functionalized using the anti-CD63, anti-CD9, and anti-CD81 capture antibodies via the PVAm/GA coupling reaction. After the coating of these antibodies, the non-specific bindings on the sensor surfaces were blocked using a bovine serum albumin (BSA)/GA composite.…”
Section: Kinetic Measurement Of Mnp-ev Bindings Using the Pc Biosensormentioning
confidence: 99%
“…Their results showed that a five‐marker panel (epidermal growth factor receptor, epithelial cell adhesion molecule (EPCAM), mucin 1, glypican 1 and wnt family member 2) showed 84% accuracy for cancer detection, which was better than the measurement based on any single‐marker detection [108]. Similarly, a photonic crystal assay was used to recognize EV surface antigens and identify macrophage‐derived EV populations [109]. In label‐free EV arrays, no fluorescence signals are produced during immunobinding reactions instead the transmission spectral shift caused by affinity combination provides the basis of detection.…”
Section: Proteomic Profiling In Evsmentioning
confidence: 99%